Seasonal variations of marine nematode assemblages in Sabah, Malaysia - Shabdin, Mohd Long; Ross, Othman (UNiversity of San Carlos, 2005)
The aim of this study was to determine the influence of heavy monsoon rainfall on the nematode species diversity on the intertidal sandy and mangroves areas. The approach taken was to perform a survey of the nematodes and certain environmental parameters of sandy and mangrove areas at Lok Kawi beach, Kota Kinabalu, Sabah, Malaysia. Two stations were established at the sandflat (S1) and mudflat (mangrove) areas (S2) of the Lok Kawi beach. Stations 1 and 2 are located at the same tidal level (Mean High Water Neap). Sampling was carried out once every two weeks for periods of 18 months. The species diversity and species richness in the sandy station were lower in February and April 1993. In the muddy station, the species diversity and number of species were lower in May 1993. The rainfall had a strong correlation with the species richness at the sandy station, and thus influenced the diversity of the nematodes. Low rainfall in the drier months (Jan to March) triggered blooms of benthic algae and caused the dominant nematode species to increase in densities. However, the number of nematodes species were reduced possibly due to high competition for food amongst the species.